Mathematical Anxiety and Resilience as an Influence of Mathematical Literacy Skills - Bilhaki, Raden Roafli; Faradillah, Ayu (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Mathematical literacy is essential for applying mathematical concepts to real-life problems, yet its development is often hindered by psychological factors such as anxiety and resilience. Mathematics anxiety negatively affects students' cognitive and problem-solving abilities, while resilience supports emotional regulation and sustained learning. This study aims to examine the combined influence of mathematics anxiety and resilience on students’ mathematical literacy. The research method used was qualitative with a phenomenological approach. The data collection process, including validity, reliability, and subject selection, was conducted using the Winstep application. Three subjects were selected according to three levels of mathematical literacy. The data analysis process involved administering tests, questionnaires, and interviews, with the test questions focusing on probability material. The results of the study indicate that students with high anxiety levels and low resilience have lower mathematics literacy scores. They are unable to complete all the ability indicators. Similarly, students with moderate anxiety and moderate resilience also showed low literacy scores. They were able to complete questions on the comprehension and representation indicators.